Lamivudine and alpha interferon combination treatment of patients with chronic hepatitis B infection: a randomised trial. Issue 4 (1st April 2000) - Schalm, S W; Heathcote, J; Cianciara, J; Farrell, G; Sherman, M; Willems, B; Dhillon, A; Moorat, A; Barber, J; Gray, D F; ,
Abstract : BACKGROUND, AIM, AND METHODS: Alpha interferon is the generally approved therapy for HBe antigen positive patients with chronic hepatitis B, but its efficacy is limited. Lamivudine is a new oral nucleoside analogue which potently inhibits hepatitis B virus (HBV) DNA replication. To investigate the possibility of an additive effect of interferon-lamivudine combination therapy compared with interferon or lamivudine monotherapy, we conducted a randomised controlled trial in 230 predominantly Caucasian patients with hepatitis B e antigen (HBeAg) and HBV DNA positive chronic hepatitis B. Previously untreated patients were randomised to receive: combination therapy of lamivudine 100 mg daily with alpha interferon 10 million units three times weekly for 16 weeks after pretreatment with lamivudine for eight weeks (n=75); alpha interferon 10 million units three times weekly for 16 weeks (n=69); or lamivudine 100 mg daily for 52 weeks (n=82). The primary efficacy end point was the HBeAg seroconversion rate at week 52 (loss of HBeAg, development of antibodies to HBeAg and undetectable HBV DNA). RESULTS: The HBeAg seroconversion rate at week 52 was 29% for the combination therapy, 19% for interferon monotherapy, and 18% for lamivudine monotherapy (p=0.12 and p=0.10, respectively, for comparison of the combination therapy with interferon or lamivudine monotherapy). The HBeAg seroconversion rates at week 52 for the combination therapy and lamivudine monotherapy were significantly different in the per protocol analysis (36% (20/56) v 19% (13/70), respectively; p=0.02). The effect of combining lamivudine and interferon appeared to be most useful in patients with moderately elevated alanine aminotransferase levels at baseline. Adverse events with the combination therapy were similar to interferon monotherapy; patients receiving lamivudine monotherapy had significantly fewer adverse events. CONCLUSIONS: HBeAg seroconversion rates at one year were similar for lamivudine monotherapy (52 weeks) and standard alpha interferon therapy (16 weeks). The combination of lamivudine and interferon appeared to increase the HBeAg seroconversion rate, particularly in patients with moderately elevated baseline aminotransferase levels. The potential benefit of combining lamivudine and interferon should be investigated further in studies with different regimens of combination therapy.